A modular dose delivery system for treating moving targets with scanned ion beams: Performance and safety characteristics, and preliminary tests. (August 2020) - Lis, Michelle; Donetti, Marco; Newhauser, Wayne; Durante, Marco; Dey, Joyoni; Weber, Ulrich; Wolf, Moritz; Steinsberger, Timo; Graeff, Christian
Highlights: Integrated the CNAO dose delivery system to the research environment of GSI. Developed a modular, motion-synchronized delivery of conformal treatment plans. Dynamic switching between plan libraries for fast, real-time dose delivery. Experimentally tested the performance and safety characteristics at CNAO. Compensated 20 mm of motion in delivery of dose cube to a gamma index result of 96%. Abstract: Purpose: The purpose of this study was to develop a modular dose-delivery system (DDS) for scanned-ion radiotherapy that mitigates against organ motion artifacts by synchronizing the motion of the beam with that of the moving anatomy. Methods: We integrated a new motion synchronization system and an existing DDS into two centers. The modular approach to integration utilized an adaptive layer of software and hardware interfaces. The method of synchronization comprised three major tasks, namely, the creation of 3D treatment plans (each representing one phase of respiratory motion and together comprising a 4D plan), monitoring anatomic motion during treatment, and synchronization of the beam to anatomic motion. The synchronization was accomplished in real time by repeatedly selecting and delivering a 3D plan, i.e., the one that most closely corresponded to the current anatomic state, until all plans were delivered. The performance characteristics of the motion mitigation system were tested by delivering 4D treatment plans to a moving phantom and comparing planned and measured dose distributions. Dosimetric performance was considered acceptable when the gamma-index pass rate was >90%, homogeneity-index value was >95%, and conformity-index value was >60%. Selected safety characteristics were tested by introducing errors during treatment and testing DDS response. Results: Acceptable dosimetric performance and safety characteristics were observed for all treatment plans. Conclusions: We demonstrated, for the first time, that a modular prototype system, synchronizing scanned ion beams with moving targets can deliver conformal, motion-compensated dose distributions. The prototype system was implemented and characterized at GSI and CNAO.